Evidence-based juvenile justice programs and practices: a critical review - Elliott, Delbert S. (Criminology & public policy, 2020)
There is growing critical commentary and debate about the relative effectiveness of individual program and generic practice approaches to identifying evidence-based interventions and their impact on the operation of the juvenile justice system. The central issue is whether both of these approaches to identifying evidence-based interventions provide a valid and reliable guide to improving juvenile justice programming and, if so, what are the relative advantages and disadvantages of each? From a public policy perspective, should we be investing more heavily in one or the other, or treating them as effective complementary approaches and encourage both? We address each of these questions and offer some suggestions for improving the effectiveness of each approach.